On Some Characteristics of Multilingualism through the Prism of the Education System - Tleuzhanova, G.K.; Tuleubayeva, Sh.K. (KU Publ., 2021)
The article considers the origin of the term «multilingualism», which has such synonyms as «plurilingualism», «polylinguism» and denotes using several languages within a particular group (a state) or using several languages by a person (a group of people). The authors present various forms and varieties of multilingualism. The necessity of taking into account and fulfilling certain conditions for the development of multilingual education is justified. The authors concluded that multilingualism is a single language system, and the principle of relying on the native language is important when learning a foreign language. Multilingual education helps to develop a tolerant attitude to the culture of another nation, and interaction, mutual understanding, as well as mutual enrichment of spiritual wealth take place while mastering a foreign language. As a result, it was identified that today linguistic and cultural diversity is considered as one of the values of the World Heritage.
Білім беру жүйесінің призмасы арқылы көптілділіктің кейбір сипаттамалары туралы
О некоторых характеристиках многоязычия сквозь призму системы образования
Keywords: multilingualism; plurilingualism; multilingual education; polylinguism; bilingualism; trilingualism; foreign language; English; characteristics